2020
DOI: 10.1155/2020/4216349
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Characterisation and Distress Diagnosis of a Metro Shield Tunnel by Adjacent Constructions

Abstract: This paper presents a case history of the developmental effect of a large-area excavation, 8 high-rise main buildings, a series of annex constructions, and ground overloaded building demolition on the deformation characteristics of an existing shield tunnel within Guangzhou Metro Line No. 1 in close proximity to the development. The shield tunnel lies in a sandy layer of the typical upper-soft and lower-hard strata in Guangzhou district, and the deformation of the tunnel has been monitored since the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Excessive elliptical deformation in shield tunnels irreparably damages concrete structures. Large lateral deformations from external loading, even if promptly unloaded, make it challenging to rectify the tunnel segment's lateral deformation [25]. This directly affects the safety margin for enduring structures like shield tunnel structures.…”
Section: Development Of Lateral Deformation Limits For Shield Tunnelsmentioning
confidence: 99%
“…Excessive elliptical deformation in shield tunnels irreparably damages concrete structures. Large lateral deformations from external loading, even if promptly unloaded, make it challenging to rectify the tunnel segment's lateral deformation [25]. This directly affects the safety margin for enduring structures like shield tunnel structures.…”
Section: Development Of Lateral Deformation Limits For Shield Tunnelsmentioning
confidence: 99%
“…e tensile result shows that the elastic modulus of the aluminium welding wire (type 1060) is 2.45 × 10 4 MPa, and it is suitable to be bent into the needed shape for its flexibility. us, we decided to select aluminium welding wire to simulate bolts and calculate the diameter and length of aluminium welding wire using equation (3). e geometric and mechanical properties of longitudinal bolts of model and prototype segmental lining are shown in Table 2.…”
Section: Advances In Civil Engineeringmentioning
confidence: 99%
“…As a result, the effect of the joints on internal forces and deformation characteristic should be taken into consideration in the design or safety evaluation of the tunnel lining. In the engineering and numerical analyses related to the underground shield-driven tunnel problems, figuring out accurately the mechanism performance of segmental linings has always been one of the major foci [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when the basement was built on the side of the existing tunnel, the diaphragm wall was more effective than the sheet pile wall in terms of controlling settlement and tensile strains of tunnels. Liu et al [24] reported that a series of hazards such as water seepage, concrete spalling, and segment cracks occurred when a station-expansion project was conducted beside the tunnels. Additionally, they further discussed the causes responsible for these hazards based on the performed numerical and theoretical investigations.…”
Section: Introductionmentioning
confidence: 99%